Genetic Basis of Fiber Improvement and Decreased Stress Tolerance in Cultivated Versus Semi-Domesticated Upland Cotton - Zhu, Guozhong; Li, Weixi; Wang, Guilin; Li, Lechen; Si, Qingxin; Cai, Caiping; Guo, Wangzhen (Frontiers in Plant Science, 2019)
Crop domestication from wild ancestors has resulted in the wide adaptation coupled with improved yield and quality traits. However, the genetic basis of many domesticated characteristics remains to be explored. Upland cotton (Gossypium hirsutum) is the most important tetraploid cotton species, accounting for about 90% of world cotton commerce. Here, we reveal the effects of domestication on fiber and stress traits through comprehensive analyses of semi-domesticated races and cultivated cotton accessions. A total of 416 cotton accessions were genotyped, and a decrease in genetic diversity from races to landraces and modern cultivars was detected. Furthermore, 71 domestication selective sweeps (DSS) and 14 improvement selective sweeps (ISS) were identified, with the Dt sub-genome experiencing stronger selection than the At sub-genome during the both selection types. The more expressed genes and a delay in the expression peak of genes related to secondary cell wall (SCW) development in modern cultivars compared to semi-domesticated cotton races, may have contributed to long fibers in these plants. However, down-regulation of genes related to stress response was responsible for decreasing stress tolerance in modern cultivars. We further experimentally confirmed that silencing of PR1 and WRKY20, genes that showed higher expression in the semi-domesticated races, drastically compromised cotton resistance to V. dahliae. Our results reveal fiber improvement and decreased stress tolerance as a result of the domestication of modern Upland cotton cultivars.